STUDY OF IN-SITU AND LABORATORY HYDRAULIC CONDUCTIVITY OF CONTAMINATED SOIL WITH OILY WASTEWATER - MEDHAT, FERZAND KAMAL AHMED; MAWLOOD, YOUSIF ISMAEL (Journal of Duhok University, 2021)
This study aims to investigate the effect of contaminated soil samples with oily wastewater which were taken from Kawergosk refinery (20 km west of Erbil city). Laboratory constant head permeability tests on contaminated soil samples with oily wastewater have been conducted. Also, One-Dimensional (1-D) and Three-Dimensional (3-D) in-situ permeability tests were performed. A noticeable decrease in the values of hydraulic conductivity coefficient (k) have been observed for Contaminated Soil Samples comparing with uncontaminated samples. Results of hydraulic conductivity coefficient obtained from one dimensional consolidation tests were increased with increasing of applied stresses. The results of field permeability tests revealed that the surrounding lands of Kawergosk refinery lies within the range of semi-permeable area for urban development while the majority part of the area lies within the range of moderate area for agricultural and conservation purposes.